Development of a Polymerase Chain Reaction Protocol for Detection of Xylella fastidiosa in Plant Tissue - Minsavage, G V; Thompson, C M; Hopkins, D L; Leite, R M V B C; Stall, R E (Phytopathology, 2025)
A 7.4-kb RI fragment of genomic DNA of strain PCE-RR (ATCC 35879) was used as a probe and was conserved in 18 strains of . The nucleotide sequence of a 1.0-kb internal RV portion of the fragment was determined, and oligonucleotides were selected for primers that amplified genomic DNA specific to in 33 strains tested by the polymerase chain reaction (PCR). Plant extracts for PCR and enzyme-linked immunosorbent assay (ELISA) were obtained by maceration of grape petioles and by vacuum extraction of citrus stems. Known cell numbers of were added to the plant extracts contained in a succinate-citrate-phosphate buffer prior to assay. Amplification of DNA by PCR was inhibited in the presence of plant extracts unless sodium ascorbate and acid-washed polyvinylpyrrolidone were added to the extraction buffer. Detection of by PCR was 100-fold more sensitive than by ELISA; the limits of detection were 1 × 10 cfu/ml for PCR and 2 × 10 cfu/ml for ELISA. Restriction endonuclease digestion of PCR amplification products with I differentiated two pathotypes of .